Two-dimensional surface EMG: The effects of electrode size, interelectrode distance and image truncation. (March 2019) - Afsharipour, B.; Soedirdjo, S.; Merletti, R.
Abstract: As the applications of High-Density surface Electromyography (HDsEMG) expand in clinical research settings, three issues deserve deeper investigation and clarification: a) the effect of electrode size, b) the effect of sampling frequency in space (interelectrode distance), c) the effect of the size of the electrode grid. The individual effects of these three factors are discussed. Electrode size introduces averaging in space, which is acceptable for electrode diameter d < 3–5 mm. Sampling frequency in space must satisfy Nyquist criterion to avoid aliasing. This implies small interelectrode distances e < 5–10 mm ( e = 10 mm is a questionable compromise between proper sampling and number of channels). The use of 1D electrode arrays or 2D electrode grids implies rectangular windowing of the signal distribution in space and generates unavoidable "truncation" effects resulting in spectral power "leakage" and aliasing. Standardization of procedures and education of the users of HDsEMG are badly needed to facilitate exchange and comparison of results.